Colorblind love and Black love on purpose: Black feminist thought, casting, and the invisibility/visibility of Black womanhood on television - Goepfert, Ava, author; Marx, Nick, advisor; Hughes, Kit, committee member; Black, Raymond, committee member (Colorado State University. Libraries, 2018)
This thesis interrogates the representations of Black womanhood on television by investigating the production context and text of two contemporary television shows. Both case studies reveal the importance of quality on screen representations and the relationship between production practices and understandings of intersectionality, stereotypes, and cultural specificity. I argue Being Mary Jane's industrial discourse and text intentionally offer a complex image of a Black woman's life while the industrial context surrounding Rachel's journey on The Bachelorette undermines Black female visibility through a colorblind discourse that dismisses Rachel's position and experience as a Black woman. These case studies demonstrate how off screen discourses contribute to representation on screen and create narratives that can exclude or include cultural specificity and racial complexity. Such narratives resonate throughout popular and political discourses with the potential to empower marginalized voices or expose the mechanisms that strive to silence them and reify white supremacy.
Keywords: casting; television; colorblind; Black feminist thought